Aerogel: Numerical Study on the Thermal and Optical Performances of an Aerogel Glazing System with the Multivariable Optimization Using an Advanced Machine Learning Algorithm (Adv. Theory Simul. 9/2019). Issue 9 (5th September 2019) - Zheng, Siqian; Zhou, Yuekuan
Abstract : A numerical model is developed to characterize the sophisticated thermal and optical performances of a novel aerogel granule translucent window. An advanced optimization engine is proposed for the optimal design and robust operation by implementing the supervised machine learning and advanced optimization algorithms. The teaching‐learning‐based optimization shows more robustness than the particle swarm optimization, for the enhancement of thermal performance. More details can be found in article number1900092 by Siqian Zheng and Yuekuan Zhou.